Compatibility of selected plant-based shortening as lard substitute: microstructure, polymorphic forms and textural properties - Abdul Manaf, Yanty Noorzianna; Marikkar, Jalaldeen Mohammed Nazrim; Mat Sahri, Miskandar; Van Bockstaele, Filip; Dewettinck, Koen; Nusantoro, Bangun Prajanto (Consejo Superior de Investigaciones Cientificas, 2017)
A study was carried out to determine the compatibility of three plant-based shortening mixtures to lard shortening (LD) in terms of microstructure, polymorphic forms, and textural properties. The shortenings of binary, ternary, and quaternary fat mixtures were prepared according to a standard procedure by blending mee fat (MF) with palm stearin (PS) in a 99:1 (w/w) ratio; avocado fat (Avo) with PS and cocoa butter (CB) in a 84:7:9 (w/w) ratio; palm oil (PO) with PS, soybean oil (SBO) and CB in a 38:5:52:5 (w/w) ratio, respectively. The triacylglycerol composition, polymorphic forms, crystal morphology, and textural properties of the shortening were evaluated. This study found that all three plant-based shortenings and LD shortening were similar with respect to their consistency, hardness and compression and adhesiveness values. However, all plant-based shortening was found to be dissimilar to LD shortening with respect to microstructure.